2006
DOI: 10.1093/qmath/hal005
|View full text |Cite
|
Sign up to set email alerts
|

Equivariant Harmonic Cylinders

Abstract: We prove that a primitive harmonic map is equivariant if and only if it admits a holomorphic potential of degree one. We investigate when the equivariant harmonic map is periodic, and as an application discuss constant mean curvature cylinders with screw motion symmetries.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(66 citation statements)
references
References 20 publications
1
65
0
Order By: Relevance
“…Hence there exists a real function η ∈ C ∞ (U) locally such that idη = dF ·F . ThenF = e −iη F is a local horizontal lift of f to S 5 (1). We can therefore assume F z · F = Fz · F = 0.…”
Section: Minimal Lagrangian Surfaces In Cpmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence there exists a real function η ∈ C ∞ (U) locally such that idη = dF ·F . ThenF = e −iη F is a local horizontal lift of f to S 5 (1). We can therefore assume F z · F = Fz · F = 0.…”
Section: Minimal Lagrangian Surfaces In Cpmentioning
confidence: 99%
“…In this section we assume that the frame is chosen as in Theorem 4.3. Then, following Burstall-Kilian ( [1]) and setting t = −x and z = x + it, we derive from (14),…”
Section: 1mentioning
confidence: 99%
“…Recently in [3,Theorem 3.4], it was shown that all equivariant primitive harmonic maps in k-symmetric spaces G/K (with an order k-automorphism τ ) are constructed from degree-one potentials:…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, all extended framings of equivariant primitive harmonic maps are obtained in this way [3,Theorem 3.4]. We note if there exists a primitive lift ψ into a k-symmetric space G/K of an equivariant primitive harmonic map φ into ã k-symmetric space G/K such thatk ≤ k and K ⊂K , then ψ must be equivariant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation